The Effect of Work Spirit and Work Discipline on Employee Performance Inregional Water Drinking Company (PDAM) Luwu District - Gaffar, Alpiana; Kusdarianto, Indra; Samsinar, Samsinar (Universitas Pamulang, 2023)
This study aims to determinethe influence of morale and work discipline on employee performance in PDAM Luwu Regency. The population of this study were all employees of the Regional Drinking Water Company (PDAM) in Luwu Regency. The sampling technique used is the questionnaire method. Namely all employees of the Luwu District Drinking Water Company (PDAM) office, totaling 40 respondents. This research lasted for 3 days, starting on Monday, December 26, 2022 by filling in a sample questionnaire until Wednesday, December 29, 2022 at the Luwu District Drinking Water Company (PDAM) office. The results of this study indicate thatWork enthusiasm and work discipline simultaneously have a significant effect on employee performance variables in PDAM Luwu Regency.Based on the results of the calculation of multiple linear regression analysis, it can be seen that the amount of contribution given by the variable morale and work discipline to employee performance at PDAM Luwu Regency simultaneously (R2) is 0.566 or 56.6%, this means employee performance is 56.6% influenced by morale and work discipline and the remaining 49.0% is influenced by other factors not examined or outside the research model.Partially, work enthusiasm has no effect on the performance of PDAM Luwu Regency employees, while dWork discipline partially has a significant effect on the performance of PDAM Luwu Regency employees.